1988
DOI: 10.1007/bf00314175
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to peripheral nerve tissue in acute Guillain-Barr� syndrome in relation to outcome of plasma exchange

Abstract: Mixed haemagglutination and complement fixation tests were used to detect serum antibodies to peripheral nerve in 36 patients with acute Guillain-Barré syndrome. Twenty patients were treated with plasma exchange, 16 served as controls. A significant antibody titre was found in 19 patients with the haemagglutination test; 30 had complement-fixing antibodies. Patients lacking complement-fixing antibodies were less disabled at entry (P less than 0.01). However, there was no correlation between the course of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These effects, however, might be caused by aspecific immune mediators rather than specific disease related factors [128]. Specific antibodies to peripheral nerve myelin are present in a widely varying proportion of patients; the proportion depends on the test and the laboratory [74,94,102,119,127,134,150,174,181,183,184]. The antigen may be a glycolipid in the myelin but it has not yet been completely identified [94,95,75].…”
Section: Immunological Aspectsmentioning
confidence: 99%
“…These effects, however, might be caused by aspecific immune mediators rather than specific disease related factors [128]. Specific antibodies to peripheral nerve myelin are present in a widely varying proportion of patients; the proportion depends on the test and the laboratory [74,94,102,119,127,134,150,174,181,183,184]. The antigen may be a glycolipid in the myelin but it has not yet been completely identified [94,95,75].…”
Section: Immunological Aspectsmentioning
confidence: 99%
“…Clinical improvement was characterized by a marked increase in muscle strength in temporal relationship to each PE. PE was performed every second day by means of an intermittent flow system (13). The average daily exchange volume was 2.5 L and a total of 12 L was exchanged during 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Koski et al (6) have reported a relationship between complement-fixing anti-peripheral nerve myelin (anti-PNM) antibody titer and the clinical course in patients with GBS. We have recently found that there is no correlation between anti-nerve antibody titer, measured by mixed haemagglutination and complement fixation techniques, and clinical course during treatment of GBS patients with PE (13). The clinical relevance of autoantibodies in GBS therefore remains uncertain.…”
mentioning
confidence: 99%